UMPSA forges strategic collaborations with 5 leading companies and institutions - Nor Salwana, Mohammad Idris (UMPSA, 2024)
KUALA LUMPUR, 11 June 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has further strengthened its relationships with industry and educational institutions through a Memorandum of Understanding/Agreement Signing Ceremony (MoU/MoA) with five leading companies and institutions, in conjunction with the MTUN Industry-Academia Discourse on Advanced TVET (MIAD) 2024.